Study of clinical-etiological profile, outcome and maternal risk-factors of birth asphyxia: a hospital based observational study - Nikhurpa, Mamta (International Journal of Research in Medical Sciences, 2022)
Background: Birth asphyxia is an important cause of neonatal morbidity and mortality. According to world health organization (WHO) out of the 130 million babies born every year, about 4 million die in the first 4 weeks of life the neonatal period. This study is aimed to assess the incidence, risk factors, complications and maternal variables associated with birth asphyxia. Methods: This is a prospective observational study conducted at pediatric newborn stabilization unit (NBSU) district hospital, Bageshwar (Uttarakhand) over a period of 12 months from January 2021 to December 2021. Total 110 newborns with no spontaneous breathing or APGAR score <7 at 5-minute requiring basic/advanced neonatal resuscitation as per NRP AHA protocol were enrolled in this study. Detailed mother’s antenatal history, risk factors along with clinical course of neonate was documented as per NICU protocol till the hospital stay in pre-designed pro-forma. Results: Total 110 newborns were admitted with incidence of 6.2% and mean birth weight of 2760±575 gm. Male gender (71%), Term delivery (82.7%), majority 85.4% neonates were revived by basic, 27.2% developed HIE grade 1. Outcome wise majority 71% (78) were discharged, 22.7% (25). Among maternal variables, majority 82.7% (91) were booked pregnancy with mean maternal age 25.69-year, multigravida 54% (59), anemia 54.5% (60) and meconium-stained amniotic fluid (MSAF) constitutes most common risk factor. Conclusions: Birth asphyxia is an important contributor of perinatal morbidity and mortality. Focus on early identification and timely management along with proper antenatal care and identification of high-risk pregnancy is crucial.